The literary theory toolkit : a compendium of concepts and methods - Rapaport, Herman, 1947- (Malden, MA : Wiley-Blackwell, 2011)
'The Literary Theory Toolkit offers readers a rich compendium of key terms, concepts, and arguments necessary for the study of literature in a critical-theoretical context. Includes varied examples drawn from readily available literary texts spanning all periods and genres Features a chapter on performance, something not usually covered in similar texts Covers differing theories of the public sphere, ideology, power, and the social relations necessary for the understanding of approaches to literature'--
'Without a proper grasp of its relevant theories, approaches, and technical language, an effective analysis and interpretation of literature can be a daunting task. The Literary Theory Toolkit offers readers a rich compendium of key terms, concepts, and arguments necessary for the study of literature in a critical-theoretical context. Author Herman Rapaport provides a lucid overview of the field of literary study and presents readers with the intellectual tools necessary to construct an effective foundation for literary analysis and a richer appreciation of world literature. Topics covered include narrative, poetic, and performance analysis; the study of textual systems; and key aspects of social theory relevant to literary study. With varied examples drawn from literary texts spanning all periods and genres, this toolkit is lively and essential reading for all students of literary theory'--
Includes bibliographical references and index.
Keywords: Literature -- History and criticism -- Theory, etc